Familial Risks of Tourette Syndrome and Chronic Tic Disorders. A Population-Based Cohort Study - Mataix-Cols, David; Isomura, Kayoko; Pérez-Vigil, Ana; Chang, Zheng; Rück, Christian; Larsson, K Johan; Leckman, James F; Serlachius, Eva; Larsson, Henrik; Lichtenstein, Paul (JAMA psychiatry (Chicago, Ill.), 2015)
Tic disorders, including Tourette syndrome (TS) and chronic tic disorders (CTDs), are assumed to be strongly familial and heritable. Although gene-searching efforts are well under way, precise estimates of familial risk and heritability are lacking. Previous controlled family studies were small and typically conducted within specialist clinics, resulting in potential ascertainment biases. They were also underpowered to disentangle genetic from environmental factors that contribute to the observed familiality. Twin studies have been either very small or based on parent-reported tics in population-based (nonclinical) twin samples. To provide unbiased estimates of familial risk and heritability of tic disorders at the population level. In this population cohort, multigenerational family study, we used a validated algorithm to identify 4826 individuals diagnosed as having TS or CTDs (76.2% male) in the Swedish National Patient Register from January 1, 1969, through December 31, 2009. We studied risks for TS or CTDs in all biological relatives of probands compared with relatives of unaffected individuals (matched on a 1:10 ratio) from the general population. Structural equation modeling was used to estimate the heritability of tic disorders. The risk for tic disorders among relatives of probands with tic disorders increased proportionally to the degree of genetic relatedness. The risks for first-degree relatives (odds ratio [OR], 18.69; 95% CI, 14.53-24.05) were significantly higher than for second-degree relatives (OR, 4.58; 95% CI, 3.22-6.52) and third-degree relatives (OR, 3.07; 95% CI, 2.08-4.51). First-degree relatives at similar genetic distances (eg, parents, siblings, and offspring) had similar risks for tic disorders despite different degrees of shared environment. The risks for full siblings (50% genetic similarity; OR, 17.68; 95% CI, 12.90-24.23) were significantly higher than those for maternal half siblings (25% genetic similarity; OR, 4.41; 95% CI, 2.24-8.67) despite similar environmental exposures. The heritability of tic disorders was estimated to be 0.77 (95% CI, 0.70-0.85). There were no differences in familial risk or heritability between male and female patients. Tic disorders, including TS and CTDs, cluster in families primarily because of genetic factors and appear to be among the most heritable neuropsychiatric conditions.